IgE as a predictor to omalizumab response in patients with chronic spontaneous urticaria - Luis Felipe Ensina; Larissa Brandão; Luisa Karla Arruda; Faradiba Sarquis Serpa; Régis Albuquerque Campos; Solange Rodrigues Oliveira Valle; Paulo Ricardo Criado; Sarbjit Singh Saini; Roberta Fachini Jardim Criado (Frontiers in Allergy)
This multicenter study aimed to explore whether baseline total immunoglobulin E (IgE) levels could predict omalizumab response in chronic spontaneous urticaria (CSU) patients. Refractory CSU patients, treated with omalizumab after failing second-generation H1-antihistamines, were analyzed retrospectively across seven centers in Brazil. The study assessed total IgE levels at baseline, comparing responders to non-responders and considering complete and partial responses. The results showed a significant reduction in CSU symptoms post-treatment. Non-responders had lower baseline IgE levels. A sensitivity of 67.8% and specificity of 93.3% for predicting a response were found at an IgE level of 59.5 IU/ml. Similar values were observed for complete responders. Notably, a baseline IgE level lower than 59.5 IU/ml may indicate late responders. The study underscores the potential of baseline IgE levels as a predictive biomarker for omalizumab response in CSU patients. Further research, incorporating diverse populations and analyzing response variables, is warranted to validate these findings.